Nitroalkanes as Versatile Nucleophiles for Enzymatic Synthesis of Noncanonical Amino Acids - Romney, David K. (ACS Catal, 2019)
C–C bond-forming reactions often require nucleophilic carbon species rarely compatible with aqueous reaction media, thus restricting their appearance in biocatalysis. Here we report the use of nitroalkanes as a structurally versatile class of nucleophilic substrates for C–C bond formation catalyzed by variants of the β-subunit of tryptophan synthase (TrpB). The enzymes accept a wide range of nitroalkanes to form noncanonical amino acids, here the nitro group can serve as a handle for further modification. Using nitroalkane nucleophiles greatly expands the scope of compounds made by TrpB variants and establishes nitroalkanes as a valuable substrate class for biocatalytic C–C bond formation.